Analisis Peran Pembiayaan Modal Usaha Pada Koperasi Kementerian Agama Kab. Langkat - Sahendra Sahendra; Abdullah Sani; Asmawarna Sinaga (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
The existence of the Ministry of Religion (Kemenag) Langkat cooperative in various regions supports the development of various business sectors, especially in the Small and Micro Medium Enterprises sector and helps the general public not to be entangled in money release institutions (loan sharks) that contain elements of usury. Akad Mudharabah as a financing product in the Ministry of Religion cooperative which is in great demand by capital managers to finance their business. however, not all Sharia cooperatives are able to implement this contract, the type of research used is a type of qualitative research. Data collection is carried out by interview and documentation methods. The results showed that the financing practice carried out by the Kemenag Langkat cooperative is the first time customers must register to become a member of the cooperative first, after being registered as a member of the cooperative customers can apply for financing, after the financing and distribution of proceeds are approved by both parties, the funds are given to the customer. The role of capital financing in the Kemenag Langkat cooperative is very meaningful for cooperative customers to develop their business. The management plays a very important role in this. The authority to provide business capital is also the full authority of the management for responsible and shirking their obligations as customers. One of the benefits felt by cooperative customers is the fulfillment of family business capital, so we can gradually improve the family economy of cooperative customers.